1980
DOI: 10.1002/1097-0142(19800315)45:5+<1248::aid-cncr2820451335>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Lymphokine-mediated immunotherapy studies in mouse tumor systems

Abstract: Studies have been performed using two subcutaneously implanted mouse tumor models to investigate the immunotherapeutic potential of lymphokine-containing culture supernatants from long-term human lymphoblast cell cultures. Human lymphoblastoid cell line, RPMI 1788, was used as a cell culture source of lymphokines. Supernatants were removed from cultures at the stationary phase of growth and concentrated on Amicon filters retaining molecules above 10,000 Daltons. This concentrate was applied to a Sephadex G-25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It has also been reported that purified recombinant human TNF shows efficacy against tumours in vivo (Sohmura et al, 1986;Palladino, 1987;Manda et al, 1987;Asher et al, 1987;Watanabe et al, 1988;Inagawa et al, 1988). However, there are few published data for in vivo studies of glycosylated human LT(gLT), (Khan et al, 1982;Papermaster et al, 1980;Ransom et al, 1982), because the production of recombinant LT with sugar moieties was not achieved until quite recently. Human lymphotoxin genomic DNA has recently been cloned, and an efficient system for producing human gLT in Chinese hamster ovary cells has now been established in our laboratory (Nakagawa et al, 1991).…”
mentioning
confidence: 99%
“…It has also been reported that purified recombinant human TNF shows efficacy against tumours in vivo (Sohmura et al, 1986;Palladino, 1987;Manda et al, 1987;Asher et al, 1987;Watanabe et al, 1988;Inagawa et al, 1988). However, there are few published data for in vivo studies of glycosylated human LT(gLT), (Khan et al, 1982;Papermaster et al, 1980;Ransom et al, 1982), because the production of recombinant LT with sugar moieties was not achieved until quite recently. Human lymphotoxin genomic DNA has recently been cloned, and an efficient system for producing human gLT in Chinese hamster ovary cells has now been established in our laboratory (Nakagawa et al, 1991).…”
mentioning
confidence: 99%
“…Several studies which used lymphokine(s) in the treatment of murine tumors have been reported (6,13,15). However, little attention has been paid to the in vivo applicability of lymphokine(s) in the control of infection with intracellular parasites.…”
mentioning
confidence: 99%